A Case with Brown-Vialetto-Van Laere Syndrome: A Sudden Onset Auditory Neuropathy Spectrum Disorder - ÇİPRUT, AYŞE AYÇA (GALENOS YAYINCILIK, 2019)
The Brown-Vialetto-Van Laere syndrome (BVVLS) is a rare neurological disorder that may present at all ages with sensorineural hearing loss, bulbar palsy and respiratory compromise. We describe a 6-yearold male patient who suffered bilateral sudden onset severe hearing loss for two years. Audiological investigations revealed sudden onset auditory neuropathy spectrum disorder bilaterally. He also had neurological complaints. During riboflavin therapy an improvement in hearing loss and the benefit of hearing aids were observed. In BVVLS, it is difficult to plan and apply auditory rehabilitation interventions and the results vary from patient to patient. In audiological evaluation, it should be borne in mind that subjective and objective tests are complemental. Early medical intervention and regular audiological follow-up are very important for effective hearing rehabilitation in the patients with BVVLS.
Keywords: Brown-Vialetto-Van Laere syndrome; riboflavin; hearing aid; auditory neuropathy spectrum disorder; VANLAERE SYNDROME; NEURONOPATHY; DEAFNESS